Flavonoid rutin presented anti-glioblastoma activity related to the modulation of onco miRNA-125b expression and STAT3 signaling and impact on microglia inflammatory profile - Lima, Irlã Santos (2024)
Coordenação de Aperfeiçoamento de Pessoal do Ensino Superior Nível (CAPES) Pro Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq). Instituto Nacional de Neurociência Translacional